2003
DOI: 10.1002/hipo.10115
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal hippocampus and classical fear conditioning to tone and context in rats: Effects of local NMDA‐receptor blockade and stimulation

Abstract: ABSTRACT:Consistent with the importance of the hippocampus in learning more complex stimulus relations, but not in simple associative learning, the dorsal hippocampus has commonly been implicated in classical fear conditioning to context, but not to discrete stimuli, such as a tone. In particular, a specific and central role in contextual fear conditioning has been attributed to mechanisms mediated by dorsal hippocampal N-methyl-D-aspartate (NMDA)-type glutamate receptors. The present study characterized the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
112
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 84 publications
(157 reference statements)
16
112
0
6
Order By: Relevance
“…Our findings that the pHPC is selectively involved in processing information about environmental cues for which there is a personal history of smoking are consistent with animal studies, in which inactivation of the analogous dorsal HPC has been shown to disrupt expression of psychostimulant CPP (Meyers et al, 2003(Meyers et al, , 2006 and CIR (Fuchs et al, 2005). These animal studies of learned reward are also consistent with human and animal fear conditioning studies, in which the dorsal HPC has been shown to have a central role in context effects (Alvarez et al, 2008;Bast et al, 2003;Maren et al, 2013;Marschner et al, 2008). Interestingly and in contrast with pHPC, aHPC exhibited greater signal in response to smoking, relative to nonsmoking, cues regardless of cue category.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings that the pHPC is selectively involved in processing information about environmental cues for which there is a personal history of smoking are consistent with animal studies, in which inactivation of the analogous dorsal HPC has been shown to disrupt expression of psychostimulant CPP (Meyers et al, 2003(Meyers et al, , 2006 and CIR (Fuchs et al, 2005). These animal studies of learned reward are also consistent with human and animal fear conditioning studies, in which the dorsal HPC has been shown to have a central role in context effects (Alvarez et al, 2008;Bast et al, 2003;Maren et al, 2013;Marschner et al, 2008). Interestingly and in contrast with pHPC, aHPC exhibited greater signal in response to smoking, relative to nonsmoking, cues regardless of cue category.…”
Section: Discussionsupporting
confidence: 87%
“…* indicates conditioning effect (CS-US pairing vs unpairing); # indicates pharmacological effect (SAL vs SCOP or SAL vs PHY) ditioning to the tone explicitly paired with shock). Previous data have shown that interfering with hippocampal processes can disrupt elemental conditioning (Bast et al, 2003). Here, we show that augmenting the hippocampal cholinergic signal not only disrupts tone fear conditioning but also promotes contextual conditioning.…”
Section: Hippocampal Ach Contributes To the Selection Of Relevant Cssupporting
confidence: 55%
“…For instance, contextual fear conditioning may depend more on the dorsal hippocampus than the ventral hippocampus [3,54,67]. In support, Lee and Kesner [49] demonstrated that all three subregions of the dorsal hippocampus (CA3, CA1, and dentate gyrus) contribute to the acquisition of contextual memory.…”
Section: Discussionmentioning
confidence: 98%
“…Although fear conditioning and PPI both depend upon the hippocampus [3,36,49,54,67,85], each task may differentially recruit subregions of the hippocampus [3,36,43,49,54,67,85]. For instance, contextual fear conditioning may depend more on the dorsal hippocampus than the ventral hippocampus [3,54,67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation